Gerardo Budowski: an innovator in land use management - Borel, Rolain (2023)
To refer to the life and work of Dr. Gerardo Budowski Wolffgang, the definition he provided about himself is very useful: "Although I have training in agriculture and forestry, I would like to call myself a land use manager" use manager”), where environmental concerns are taken into account towards the sustainable management of natural renewable resources.” Of course one could add more qualifiers to Budowski's various contributions in the second half of the 20th century. However, the quote above sums them up very well, and in a few keywords: renewable resources, land use and sustainable management, with its three "legs" or dimensions: environmental, economic and social. Budowski's career headed in that direction, somewhat surprisingly, starting from a base with a productive agricultural and forestry focus. For someone with less vision and ability than him, this platform could have led to a very different and probably less extensive journey.